2021
DOI: 10.1080/20932685.2021.1930097
|View full text |Cite
|
Sign up to set email alerts
|

The neglected unity-in-variety principle: A holistic rather than a single-factor approach in conceptualising a visual merchandise display

Abstract: While retailers cannot stress enough the fact that, in reality, a variety of store design cues combine to make a merchandise's visual display (VMD), the product presentation research focuses mostly on investigating the effect of a single retail display cue, at a time, on consumer product evaluations. But, is "unity-in-variety" a neglected principle in the product presentation research? Scholars are increasingly suggesting more systematic study to identify combinations of key store cues that shape a product's d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Liu, Wu et al, 2022;R. Post et al, 2017), atmospherics of stores (Jang et al, 2018;Logkizidou, 2021), arrangements of objects (Van Geert & Wagemans, 2021), and a variety of products, such as chairs (Loos et al, 2022), clothes (Gray et al, 2014), and motorcycles (Nasar, 1987;R. A. G. Post et al, 2016).…”
Section: Tactile Consumer Experiencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu, Wu et al, 2022;R. Post et al, 2017), atmospherics of stores (Jang et al, 2018;Logkizidou, 2021), arrangements of objects (Van Geert & Wagemans, 2021), and a variety of products, such as chairs (Loos et al, 2022), clothes (Gray et al, 2014), and motorcycles (Nasar, 1987;R. A. G. Post et al, 2016).…”
Section: Tactile Consumer Experiencesmentioning
confidence: 99%
“…The principle of UiV has received a significant amount of empirical support in the visual domain. The principle has been found to apply in the esthetic visual experience produced by things such as abstract patterns (Muth et al, 2021), web pages (Deng & Poole, 2012; W. Liu, Wu et al, 2022; R. Post et al, 2017), atmospherics of stores (Jang et al, 2018; Logkizidou, 2021), arrangements of objects (Van Geert & Wagemans, 2021), and a variety of products, such as chairs (Loos et al, 2022), clothes (Gray et al, 2014), and motorcycles (Nasar, 1987; R. A. G. Post et al, 2016). While UiV has not been empirically tested in the tactile domain fundamental psychological and brain research provides some indication that perceptual processes related to UiV in the visual domain may be shared with the tactile domain.…”
Section: Tactile Consumer Experiencesmentioning
confidence: 99%
“…Early literature relevant to aesthetics that we have focused on is predominantly centered around abstract stimuli (Berlyne, 1972;Berlyne & Boudewijns, 1971). Subsequent research focused on product aesthetics (Logkizidou, 2021;Loos et al, 2022;Post et al, 2017;Post et al, 2013, August). In these studies, a negative correlation between unity and variety was observed, yet both factors positively impacted the aesthetic appreciation of the product.…”
Section: 1the Perceptual Level: Unity and Varietymentioning
confidence: 99%